Analysis of the Effect of Pressing Pressure Variations to Physical Characteristics and Expansion Performance of Cocopeat Blocks - Ratmono Hari Widyatmoko; Fransiska Karlentina Hapsari; Tri Hannanto Saputra; Dionisius Wisnu Pratama; Hendrawan Adi Nugroho; Rosy Eka Saputra (P3KM Politeknik Pertanian Negeri Samarinda, 2026)
Cocopeat, a by-product of coconut coir, has great potential as an environmentally friendly planting medium because it has high water absorption and retention. The handling of bulk cocopeat poses logistical challenges in storage and distribution. This study aims to determine the minimum pressure and compressive force required to form a stable cocopeat block as the basis for the design of a pressing machine. The experiment was carried out using hydraulic pressure variations of 10 to 50 bar with a holding time of 10 seconds, utilizing the initial volume of cocopeat of 8 liters in a mold with dimensions of 200 × 200 mm. To ensure the reliability of the data, each variation was tested on three specimens. Evaluation parameters include block thickness, durability of drop test, and rehydration (expansion). The results showed that the increased pressure significantly lowered the block thickness from 90.78 mm (10 bar) to 56 mm (50 bar) through increased material compaction. The low standard deviation (1.32–1.50 mm) confirms the high dimensional consistency between specimens. Blocks pressed at pressures of 10–20 bar fail the drop test, while pressures between 30–50 bar result in a sturdy, structurally stable block. After 5 liters of water were added, the entire sample managed to expand back to a final volume ranging from 9.55–9.85 liters. A pressure of 30 bar, which produces a force of 184,725 N, is recommended as the optimal design base; This value is sufficient to produce a resilient Cocopeat block that passes the drop test while optimizing the mechanical force requirements of the engine.